2007
DOI: 10.4049/jimmunol.178.1.511
|View full text |Cite
|
Sign up to set email alerts
|

IL-13 Is Pivotal in the Fibro-Obliterative Process of Bronchiolitis Obliterans Syndrome

Abstract: Acute allograft rejection is considered to be a predominately type 1 immune mediated response to the donor alloantigen. However, the type 2 immune mediated response has been implicated in multiple fibroproliferative diseases. Based on the fibro-obliterative lesion found during bronchiolitis obliterans syndrome (BOS), we hypothesized that the type 2 immune mediated response is involved in chronic lung allograft rejection. Specifically, whereas acute rejection is, in part, a type 1 immune response, chronic rejec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
44
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 39 publications
5
44
1
Order By: Relevance
“…Prior studies have provided considerable evidence that targeting the IL-13 pathway may be a way of controlling pulmonary inflammation and fibrosis, which are recognized as key pathological changes in a broad spectrum of respiratory diseases, including asthma (25), bronchiolitis obliterans syndrome (26), and interstitial lung diseases (27). In the current study, we detected increased levels of IL-13 in lung homogenates of mice exposed to silica particles 28 d postchallenge.…”
Section: Discussionsupporting
confidence: 57%
“…Prior studies have provided considerable evidence that targeting the IL-13 pathway may be a way of controlling pulmonary inflammation and fibrosis, which are recognized as key pathological changes in a broad spectrum of respiratory diseases, including asthma (25), bronchiolitis obliterans syndrome (26), and interstitial lung diseases (27). In the current study, we detected increased levels of IL-13 in lung homogenates of mice exposed to silica particles 28 d postchallenge.…”
Section: Discussionsupporting
confidence: 57%
“…21 Furthermore, numerous studies in cytokinedeficient mice and using neutralizing antibodies have demonstrated that the development of the CD4 + Th2 cell response, including the local production of IL-4 and IL-13, is strongly associated with liver fibrosis, 22,23 scleroderma, 24 and pulmonary fibrosis. [25][26][27] Stimulation of cultured fibroblasts with IL-4 or IL-13 triggers upregulation of the expression of the extracellular matrix proteins type I and III collagen. [28][29][30] Despite this, to the best of our knowledge, this study is the first report demonstrating that CD4 + Th2 cells play a key role in renal fibrosis and that a CRTH2 antagonist can slow the progression of renal fibrosis by suppressing the Th2 cell response.…”
Section: Discussionmentioning
confidence: 99%
“…The profibrotic type 2 helper T cell cytokine IL-13 is critical in the development of luminal obliteration in animal models of BO, 4,26 and increased levels of IL-13 are present in BAL fluid of human lung transplant recipients with BOS. 26 Previously, myofibroblasts in human BO lesions expressed IL-13 receptor ␣1, the receptor chain necessary for signaling by IL-13.…”
Section: Lr-mscs Isolated From Normal Human Lung Allografts Demonstramentioning
confidence: 99%
“…26 Previously, myofibroblasts in human BO lesions expressed IL-13 receptor ␣1, the receptor chain necessary for signaling by IL-13. 4 LR-MSCs demonstrated significant expression of this receptor by both flow cytometry and immunofluorescence microscopy ( Figure 2, A nofluorescence (P Ͻ 0.0001, Figure 2C).…”
Section: Lr-mscs Isolated From Normal Human Lung Allografts Demonstramentioning
confidence: 99%